1993
DOI: 10.1017/s0954579400006246
|View full text |Cite
|
Sign up to set email alerts
|

Resilience is not a unidimensional construct: Insights from a prospective study of inner-city adolescents

Abstract: The maintenance of high social competence despite stress was examined in a 6-month prospective study of 138 inner-city ninth-grade students. The purpose was to provide a replication and extension of findings derived from previous cross-sectional research involving a comparable sample of children. Specifically, goals were to examine the extent to which high-stress children with superior functioning on one or more aspects of school-based social competence could evade significant difficulties in (a) other spheres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
160
0
11

Year Published

1998
1998
2018
2018

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 258 publications
(185 citation statements)
references
References 33 publications
(48 reference statements)
10
160
0
11
Order By: Relevance
“…As such, determination and description of resilience should not rely on a single domain. It is being increasingly recognized that competence in one domain does not preclude difficulties in other domains of functioning (Luthar, Doernberger, & Zigler, 1993; Masten, 2014; Southwick et al, 2014). It has also been suggested that resilience should be further separated into different facets (Hobfoll et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…As such, determination and description of resilience should not rely on a single domain. It is being increasingly recognized that competence in one domain does not preclude difficulties in other domains of functioning (Luthar, Doernberger, & Zigler, 1993; Masten, 2014; Southwick et al, 2014). It has also been suggested that resilience should be further separated into different facets (Hobfoll et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…While such an examination of the presence or absence of resilience has great utility, resilience may, in fact, be multidimensional in nature. That is, within an individual, adaptive functioning may vary across domains and in different contexts (Freitas & Downey, 1998;Luthar, Doernberger, & Zigler, 1993). …”
mentioning
confidence: 99%
“…Nos ano 1990, duas gerações de pesquisadores começaram a estudar, paralelamente, a capacidade de resistência e/ou invulnerabilidade de indivíduos ao stress relacionado à condição de vida adversa que tinham (LUTHAR, 1993).…”
Section: Resiliênciaunclassified